KEPEMIMPINAN YANG BERBUDAYA (Studi di Desa Boti Kecamatan Kie Kabupaten Timor Tengah Selatan) - Saingo, Yakobus Adi; Se’u, Windynia G. G.; Manu, Lukas; Sette, Gusti Y.; Lopo, Yismaya D. (Studi Budaya Nusantara, 2022)
This study aims to explore in depth the concept of cultural leadership in the Boti tribe. This study uses a qualitative research design with a thematic analysis approach. The informants in this study were the leader of the boti tribe who were called